2009
DOI: 10.1111/j.1479-828x.2009.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion for caesarean delivery complicated by placenta praevia

Abstract: Gestational age at delivery and type of surgery required are predictors of transfusion during caesarean for placenta praevia. Arterial balloon occlusion does not appear to increase transfusion risk and may be considered as one of the techniques in management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…One study showed that anterior placenta previa was associated with increased risk of excessive blood loss and massive transfusion irrespective of confounding factors [11]. In other studies [12,13], increased risk of hemorrhage in anterior placenta previa was related mainly to the presence of placenta accreta, especially among women with previous cesarean delivery. The main strength of the present study is that it included only women with anterior placenta previa and excluded those with placenta accreta.…”
Section: Discussionmentioning
confidence: 97%
“…One study showed that anterior placenta previa was associated with increased risk of excessive blood loss and massive transfusion irrespective of confounding factors [11]. In other studies [12,13], increased risk of hemorrhage in anterior placenta previa was related mainly to the presence of placenta accreta, especially among women with previous cesarean delivery. The main strength of the present study is that it included only women with anterior placenta previa and excluded those with placenta accreta.…”
Section: Discussionmentioning
confidence: 97%
“…The risk factors for blood transfusion were maternal age greater than 34 years, a history of more than one dilatation and curettage, and complete placenta praevia (ORs 3.7, 4.8 and 26, respectively). (10) Subsequently, Boyle et al (11) reported that 71 (34%) of 206 patients with placenta praevia received a blood transfusion during Caesarean section but reported the risk factors to be gestational age of 32-35 weeks at delivery and Caesarean hysterectomy (ORs 2.6 and 29.4, respectively). (11) In these studies, 5.5%-10.6% of the placenta praevia patients also presented with placenta accreta, which may be a confounding factor for massive haemorrhage and the need for a blood transfusion.…”
Section: Placenta Praevia Increased the Risk Of Peripartum Blood Tranmentioning
confidence: 99%
“…(10) Subsequently, Boyle et al (11) reported that 71 (34%) of 206 patients with placenta praevia received a blood transfusion during Caesarean section but reported the risk factors to be gestational age of 32-35 weeks at delivery and Caesarean hysterectomy (ORs 2.6 and 29.4, respectively). (11) In these studies, 5.5%-10.6% of the placenta praevia patients also presented with placenta accreta, which may be a confounding factor for massive haemorrhage and the need for a blood transfusion. As a result, our transfusion rate in pure placenta praevia pregnancies (19%) was lower than those of the aforementioned studies.…”
Section: Placenta Praevia Increased the Risk Of Peripartum Blood Tranmentioning
confidence: 99%
See 1 more Smart Citation
“…Olsen et al [17] retrouvent également un taux de transfusions conséquent avec un nombre de concentrés globulaires transfusés (4 culots en moyenne) plus élevé que dans notre série. Kavak [24], l'utilisation du BB n'augmente pas le taux de transfusion en cas de césarienne avec placenta praevia.…”
Section: Discussionunclassified